The prohibition of the principle of opportunity in crimes against the public administration committed by officials - Pezo Jimenez, Omar (2020)
The implications of the prohibition of the principle of opportunity in Cases of Crimes of culpable peculation , is a research type applied to seek Give a proposed solution in relation to a prohibitory rule of the Criminal Procedure Code that seriously affects our judicial system Generating load procedure in Our public institutions and by preventing payment of civil damages so fast, way is I get to know scientifically important information about the procedural burden on Crimes of Corruption of public Officials and even more so on the speed of the payment of Civil repairs State a favor , very alarming being generated numbers for various factors mentioned in this thesis